Reference ranges of myocardial performance index from 12 to 40 weeks of gestation - Luewan,S. (Springer Verlag, 2015)
OBJECTIVE: To establish reference ranges of fetal myocardial performance index (MPI) in normal singleton pregnancies from 12 to 40 weeks gestation. DESIGN: Prospective descriptive study. SETTING: A tertiary care teaching center in the Northern part of Thailand. PARTICIPANTS: A total of 562 normal singleton pregnancies at 12-40 weeks of gestation. INTERVENTION: Fetal echocardiography was performed for isovolumetric contraction time, isovolumetric relaxation time, ejection time and MPI by one experienced sonographer, using strict criteria for measurement. The measured MPI values were regressed against gestational age (GA) and biparietal diameter (BPD) to determine the best-fitted model. PRIMARY OUTCOME MEASURES: MPI for each gestational week and each BPD point (cm). RESULTS: A total of 562 measurements were successfully obtained with good-quality Doppler tracings and complete data for analysis. Predicted mean of MPI for GA and BPD is as follows: predicted mean MPI = 0.404 + 0.004 × GA (weeks) (r (2) = 0.143, p < 0.001) and = 0.419 + 0.015 × BPD (cm) (r (2) = 0.139, p < 0.001) as functions of GA and BPD, respectively. The predicted SD of MPI for GA and BPD is constant throughout pregnancy, 0.071348 and 0.073440, respectively. CONCLUSION: MPI is significantly increased with GA. The reference ranges of MPI according to GA and BPD, as a marker in evaluating global cardiac function between 12 and 40 weeks of gestation was constructed.